Determinants of enforced and voluntary tax compliance: Adopting slippery slope framework - Tahar, Afrizal; Bandi, Bandi (Journal of Accounting and Investment, 2024)
Research aims: This research aims to scrutinize the influence of factors impacting voluntary tax compliance and enforced tax compliance using the variables of power of authorities and trust in authorities.Design/Methodology/Approach: This study employed a research sample of Micro, Small, and Medium Enterprises (MSMEs) taxpayers in the Special Region of Yogyakarta represented by business school students, utilizing a questionnaire survey via Google Form with a purposive sampling method. The total number of questionnaires distributed was 60 questionnaires, with 59 questionnaires that could be processed. Data analysis was then carried out using the partial least squares (PLS) approach.Research findings: The results of this study demonstrated that using the slippery slope framework theory, trust in authorities was positively associated with voluntary tax compliance, while the power of authorities was negatively associated with voluntary tax compliance. Trust in authorities, however, did not have any impact on enforced tax compliance. Additionally, the power of authorities exerted a positive effect on voluntary tax compliance.Theoretical contribution/Originality: This study provides an understanding of the factors influencing tax compliance by referring to the slippery slope framework theory. Apart from that, this research field is still relatively underexplored in Indonesia.Practitioner/Policy implication: This study can be used to determine the factors driving and inhibiting MSMEs' taxpayer compliance so that it can be used as input and consideration to improve services related to taxpayer compliance further.Research limitation/Implication: This study can serve as a valuable resource for future research and the generation of new ideas. Also, it can be utilized as a reference in educational materials pertaining to aspects that promote taxpayer compliance.